Exact solution of one boundary-value problem - Botyuk, A. O. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We study the boundary-value perlodic problem u tt −u xx =F(x, t), u(0, t)=u(π, t)=0, u(x, t+T)=u(x, t), (x, t) is R 2. By using the Vejvoda-Shtedry operator, we determine a solution of this problem.